The Role of Students in Realizing Justice in Community Life - Yunita, Sri; Pebrija, Putri; Tessalonika, Jelita; Khairani, Dewi; Mian, Mian (Lafadz Jaya Publisher, 2023)
Many societal injustices occur due to lack of education/awareness in society. This makes society blind to justice. The purpose of this research reveals the importance of the role of students in realizing justice in society. The method used by researchers is the descriptive method by collecting library data, reading and taking notes in carrying out journal preparation. The results achieved are that students have an important role in realizing justice in society.